Benchmarking Tilapia Aquaculture Systems in Egypt: Synergies, Trade-offs, and Entry Points for Sustainable Development - Rossignoli, Cristiano; Shikuku, Kelvin Mashisia; Manyise, Timothy; Nasr-Allah, Ahmed; Henriksson, Patrik; Dam Lam, Rodolfo; Lozano, Denise; Tran, Nhuong; Roem, Arjen; Badr, Alaa; Sbaay, Ashraf; Calmet, Maria; et al. (2023)
The growing demand for aquatic foods requires the sustainable intensification of aquaculture systems. However, policy and investment decisions for sustainable intensification of aquaculture systems are often hindered by a lack of benchmarking data related to performance of such systems. Abstract accepted and presented at WAS2022 – published in the book of abstracts at pag 606.